1992
DOI: 10.1002/mcs.1220040308
|View full text |Cite
|
Sign up to set email alerts
|

Extended use of solvent venting injection techniques for large sample volumes and coupled capillary columns in SFC

Abstract: Abstract. The solvent venting injection technique has been tested for 1-pL injections of lipids in open tubular column SFC. No sample loss during solvent venting was experienced with a 7-m precolumn at elevated temperatures. The solvent venting technique has also been combined with gas purging to concentrate the sample on-line with SFC. Injections totalling 10-50 pL of sample have been performed. The solvent venting technique with minor modifications in the instrumentation was utilized for group separations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The SFC instrument consisted of one ISCO 260 D pump (Lincoln, Nebraska, USA) and two SFC/GC ovens [8] The solvent was vented via the 6-port valve with helium gas. Gas purging of the solvent, which utilized 100 pm i.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SFC instrument consisted of one ISCO 260 D pump (Lincoln, Nebraska, USA) and two SFC/GC ovens [8] The solvent was vented via the 6-port valve with helium gas. Gas purging of the solvent, which utilized 100 pm i.…”
Section: Methodsmentioning
confidence: 99%
“…The sample is injected several times and the solvent is purged from the retention gap with helium gas each time [8]. This technique is illustrated in Figure 6.…”
Section: Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample recovery can be quite acceptable with this technique. For example, Berg et al [24] reported 100 % recovery of diglycerides. They used a 7-m × 50-µm-ID precolumn to introduce 1µl samples onto 50-µm-ID columns.…”
Section: Solvent Venting Under Supercritical Conditionsmentioning
confidence: 99%
“…Another gas-purging method, with helium, made use of a 1.5-m × 100-µm-ID uncoated retention gap [24]. By injecting 1 µl samples of glycerides, triglycerides were completely recovered, while diglycerides suffered a 30 % loss.…”
Section: Solvent Venting Under Reduced Pressurementioning
confidence: 99%